Legal Protection For Advocates Who Are Considered Not In Good Faith For Alleged Obstruction Of Justice In Corruption Cases - Erwan Budi Herianto; Handoyo Prasetyo; Slamet Tri Wahyudi (Yayasan Multidimensi Kreatif, 2024)
Advocates as one of the professions in the field of law in their duty to defend clients both inside and outside the trial are equipped with privileges in the form of legal protection (immunity), but often these privileges are abused by advocates by obstruction of justice especially in cases of corruption crimes that aim to prevent clients from being investigated by Police Investigators, the Prosecutor's Office or the KPK. There are differences in the parameters of the assessment of good or bad ethics by an Advocate carried out by the Investigator so that it is considered to be an obstruction of justice so that there is a conflict between the legal norms contained in Article 16 of Law Number 18 of 2003 concerning Advocates and the reality that occurs in the field. The problem that causes advocates to be considered not to be good at obstructing justice in corruption cases is due to the absence of assessment parameters of advocates who are not in good faith and the absence of legal protection for advocates who are suspected of obstruction of justice, especially in corruption cases. The method used in this study is normative - empirical legal research, using a case approach, a legislative approach (statue approach) and a conceptual approach (Conceptual Approach). This study aims to examine the assessment parameters of advocates who do not have good faith against the suspicion of obstruction of justice by investigators and to find out the analysis of legal protection (immunity rights) owned by advocates who are considered to have no good faith by committing obstruction of justice, especially in cases of corruption. The results of this study are that the criteria for Advocates who are considered not in good faith are violations of the code of ethics, laws and regulations, oath or promise of Advocates as well as the value of feasibility and propriety. In addition, in order to create legal protection and certainty, a special institution such as the Advocate Honorary Council is needed which aims to determine whether the actions of the Advocate who are considered not to be in good faith are contrary to the etic code or laws and regulations or not.